In Vitro Activity of Ceftazidime-NXL104 against 396 Strains of β-Lactamase-Producing Anaerobes - Citron, Diane M. (American Society for Microbiology, 2011)

(untitled)
NXL104, a novel β-lactamase inhibitor, was tested at a constant concentration of 4 μg/ml in combination with ceftazidime (CAZ), with and without added metronidazole, against 396 β-lactamase-producing strains of anaerobic bacteria. MIC(50)/MIC(90) values for Bacteroides fragilis and the B. fragilis group were 8/16 and 64/>128 μg/ml, respectively. Although CAZ-NXL104 had limited activity against most anaerobic strains, in combination with metronidazole it shows potential for treating mixed infections involving resistant Enterobacteriaceae and anaerobes.